Genetic diversity of Kıvırcık sheep breed reared in different regions and its relationship with other sheep breeds in Turkey - Yasemin Öner (Italian Journal of Animal Science, 2014)
In this study, animals from the Kıvırcık breed of sheep and two closely related breeds (Pırlak and Karacabey Merino) were analysed by using 15 microsatellite markers to evaluate the genetic diversity within the Kıvırcık breed and to elucidate its relationship with the other two breeds. A total of 244 alleles were detected on all of the 15 microsatellite loci studied. While the Kıvırcık population of sheep showed a significant deviation from the Hardy- Weinberg equilibrium (HWE) for all 15 loci, both the Pırlak and Karacabey Merino breeds showed a significant deviation from the HWE for 10 loci. The mean observed heterozygosity and FIS exhibited ranges of 0.63 to 0.72 and 0.0672 to 0.2139, respectively. The highest mean number of alleles value and the greatest number of private alleles were observed in the Kıvırcık population. While microsatellite analysis revealed high genetic diversity in breeds investigated, a high level of inbreeding was also observed between different Kıvırcık populations and other two breeds. The genetic differentiation between breeds was found to be low. The Kıvırcık from Istanbul and Bursa were the most closely related genetically, while the Kıvırcık from Manisa differed from the other populations. In addition, the Karacabey Merino and Pırlak breeds grouped together.